Goose and duck share tasks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Imele Benoit, a meat technologist in Bamenda, Cameroon, tells us about his incubating ducks: 'I have a small but diversified poultry run, with chickens and cocks, ducks and drakes and geese and ganders, all free-range.I have noticed that the geese...